Sorting out the Superbugs: Potential of Sortase A Inhibitors among Other Antimicrobial Strategies to Tackle the Problem of Antibiotic Resistance - Zrelovs, Nikita (Antibiotics (Basel), 2021)
Rapid spread of antibiotic resistance throughout the kingdom bacteria is inevitably bringing humanity towards the “post-antibiotic” era. The emergence of so-called “superbugs”—pathogen strains that develop resistance to multiple conventional antibiotics—is urging researchers around the globe to work on the development or perfecting of alternative means of tackling the pathogenic bacteria infections. Although various conceptually different approaches are being considered, each comes with its advantages and drawbacks. While drug-resistant pathogens are undoubtedly represented by both Gram(+) and Gram(−) bacteria, possible target spectrum across the proposed alternative approaches of tackling them is variable. Numerous anti-virulence strategies aimed at reducing the pathogenicity of target bacteria rather than eliminating them are being considered among such alternative approaches. Sortase A (SrtA) is a membrane-associated cysteine protease that catalyzes a cell wall sorting reaction by which surface proteins, including virulence factors, are anchored to the bacterial cell wall of Gram(+) bacteria. Although SrtA inhibition seems perspective among the Gram-positive pathogen-targeted antivirulence strategies, it still remains less popular than other alternatives. A decrease in virulence due to inactivation of SrtA activity has been extensively studied in Staphylococcus aureus, but it has also been demonstrated in other Gram(+) species. In this manuscript, results of past studies on the discovery of novel SrtA inhibitory compounds and evaluation of their potency were summarized and commented on. Here, we discussed the rationale behind the inhibition of SrtA, raised some concerns on the comparability of the results from different studies, and touched upon the possible resistance mechanisms as a response to implementation of such therapy in practice. The goal of this article is to encourage further studies of SrtA inhibitory compounds.